Disaster Management and Post-quake Impact on Tourism in Nepal (The Gaze: Journal of Tourism and Hospitality, 2016)
Tourism, a large and unique collection of industry sectors is an expanding worldwide phenomenon. By the next century, tourism will be the single largest industry in the world with special needs in disaster planning and recovery. Tourism is vulnerable sector that has been experiencing major crises from disasters. No tourist destination is immune to such crises. Nepal is one of the world’s 20 most disaster-prone countries where earthquakes are unique challenges for tourism. Nepal has to be very optimistic about the future of tourism as it has huge potentials to be the top class tourist destinations. Nepal should target to the global tourism market and take serious efforts to convince foreigners to visit Nepal and revive immediately. The Nepali tourism industry requires a strategy that will help manage crises and rapidly implement recovery strategies.The Gaze: Journal of Tourism and Hospitality Vol.7 2015 pp.37-57